The Influence of Dental Status and Blood Parameters Characterizing Endogenous Intoxication on the Timing of Childbirth - Maria Hakobyan; Gayane Manrikyan; Marina Markaryan; Izabella Vardanyan; Mikayel Manrikyan (Medicina, 2024)
Background and Objectives: Epidemiological and microbiological–immunological studies have led to the conclusion that periodontal disease may be a risk factor for preterm birth. The aim of this study was to investigate and identify the relationship of some hematological cellular biomarkers characterizing the chronic oral focus of infection with pregnancy outcomes and their impact on those outcomes. Materials and Methods: Clinical and laboratory tests were conducted on 100 pregnant women, grouped by full-term or preterm births, with the assessment of the following markers: DMF, CPI and PIRI, PHP, microbiological examination of periodontal pockets and amniotic fluid, WBS count, WBCSI, LGI, and NMR. A statistical analysis was carried out with SPSS Statistics version 19.0. Results: Women with preterm labor had higher-grade caries (CSL > 0.3), while women with full-term childbirth had moderate caries (CSL < 0.3). A satisfactory level of oral hygiene efficiency was found in 50% (group 1) and 38.1% (group 2) of the expectant mothers. The periodontal status by the PIRI showed tissue lesions in 20.7% (group 1) and 92.9% (group 2) of the women. The WBCSI was 2.27 ± 0.82 and 2.15 ± 0.68, the NMR was 9.29 ± 5.119 and 11.62 ± 7.78, and the LGI was 3.54 ± 1.1 and 3.73 ± 0.81 in groups 1 and 2, respectively. Comparative analysis of bacterial contamination of the amniotic fluid revealed the predominance of Fusobacterium nucleatum (64.3%), Tannerella forsythia (57.1%), Prevotella intermedia (50%), Porphyromonas gingivalis (57.1%), Staphylococcus aureus (45.2%), and Candida albicans (50%) in women with premature birth. Conclusions: In women with preterm birth, the values of the indices characterizing a chronic oral focus of infection evoke more significant correlations with the timing of delivery, which indicates the significant role of an oral focus of infection. The presence of microbial invasion of amniotic fluid may indicate the role of periodontopathogenic bacteria in pregnant women diagnosed with a risk of preterm birth.